(untitled) (American Journal of Islam and Society, 2009)
Despite the central importance of festival and devotional piety to premodern Muslims, book-length studies in this field have been relatively rare. Katz’s work, The Birth of the Prophet Muhammad, represents a tour-deforce of critical scholarship that advances the field significantly both through its engagement with textual sources from the formative period to the present and through its judicious use of theoretical tools to analyze this material. As its title suggests, the work strives to explore how Muslims have alternatively promoted and contested the commemoration of the Prophet’s birth at different points in history, with a particular emphasis on how the devotionalist approach, which was prominent in the pre-modern era, fell out of favor among Middle Eastern Sunnis in the late twentieth century. Aimed primarily at specialists in Middle Eastern and Islamic studies, especially scholars of history, law, and religion, this work is recommended to anyone interested in the history of Muslim ritual, the history of devotion to the Prophet, and the interplay between normative and non-normative forms ofMuslim belief and practice ...